The induced cryptic metabolites and antifungal activities from culture of Penicillium chrysogenum by supplementing with host Ziziphus jujuba extract. (November 2022) - Li, Shi-Yu; Yang, Xue-Qiong; Chen, Jing-Xin; Wu, Ya-Mei; Yang, Ya-Bin; Ding, Zhong-Tao
Abstract: The productions of cryptic metabolites including three undescribed drimane sesquiterpenoids, penicichrins A-C, and three known compounds from Penicillium chrysogenum were activated by the host Ziziphus jujuba medium. The structures were established by comprehensive analysis of spectroscopic data. The spiro β -lactone, and gem-dimethyl dihydroxylation in induced penicichrins A-C were rare in natural products. Cryptic metabolites, monaspurpurone was first found in Penicillium . 4-Methoxy-3-methylgoniothalamin, and 2-hydroxy-l-phenyl-l, 4-pentanedione were second example of isolation. Penicichrin A, monaspurpurone, 4-methoxy-3-methylgoniothalamin, physcion, ergosterol, and ergosta-7, 22-dien-3 β -ol had antifungal activities against phytopathogens, P. chrysogenum, Alternaria alternata and Aspergillus fumigatus with MICs ≤2 μg/mL, and 2-hydroxy-l-phenyl-l, 4-pentanedione had flowering activity. So the chemical constituents from Z. jujuba could induce the productions of cryptic metabolites with plant growth-promoting activity from endophyte P. chrysogenum . Graphical abstract: Image 1 Highlights: Cryptic metabolites including three undescribed ones were found from P. chrysogenum by host medium. The spiro β -lactone, and gem-dimethyl dihydroxylation in penicichrins were rare in natural products. The induced compounds indicated plant growth-promoting activities.